Efeito de progesterona e benzoato de estradiol na dinâmica folicular e produção in vitro de embriões bovinos. - Alexandre Floriani Ramos (2006)
The purpose of this study was to evaluate the effect of estradiol benzoate (EB) and progesterone/norgestomet on follicular dynamics of heifers aspirated every 7 d through synchronization of the follicular wave emergence in order to increase the number of follicles and quality of the recovered oocytes. Three experiments were designed in which crossbred Simmental x Nelore heifers were randomly divided into three groups, with all animals participating in all groups. In experiments 1 and 2, heifers were synchronized using a progestin implant for 7 d followed by a 150 µg im injection of d-Cloprostenol and aspiration of all ovarian follicles greater than 3 mm in diameter. In experiment 1 (n = 12), follicles from group 2X were aspirated twice a week with 4- and 3-day interval, and follicles from 1X and 1X-EB heifers were aspirated once a week. Heifers from group 1X-EB also received an im injection of 2 mg of EB immediately after OPU. In experiment 2 (n= 12), all heifers were aspirated once a week. Heifers from 0EB group did not receive EB, and from 2EB and 5EB received 2 mg and 5 mg of EB immediately after OPU. In experiment 3 (n = 15), heifers were synchronized with 2 mg EB and progesterone intravaginal implant (DIB) for seven d followed by an im PGF2_ injection. On day 4 of the subsequent estrous cycle, heifers received a DIB and had all ovarian follicles larger than 3 mm in diameter aspirated, followed by a PGF2_ injection on day seven. Heifers in groups 0h-EB (n = 4), -12h-EB (n = 6) and -24h-EB (n = 5) received 2 mg of EB immediately after OPU and twelve and twenty four h before, respectively. The semen, media used and culture conditions were equal for all groups. Ultrasound evaluations of number of follicles greater than 3 mm in diameter and size of the largest follicle at the time of OPU were performed. All recovered oocytes were in vitro matured and fertilized (D0). Cleavage rate on D2 and blastocyst production on D7 was evaluated. During a 7-day period, daily measurement of the size of the greatest follicle was performed by ultrasonography, and daily blood collection was done for evaluation of serum FSH concentrations. Although the use of EB in association with a norgestomet/progesterone implant seven d prior to OPU have altered follicular wave profile and FSH concentration, it was not able to efficiently synchronize the emergence of follicular wave and follicular deviation. Moreover, it was not enough to improve number and quality of the recovered oocytes. This study failed to demonstrate a positive effect of OPU earlier after wave emergence, when the effect of dominance should be less pronounced, on IVP in bovine. Moreover, the use of EB in association with a progesterone implant 12 and 24 h prior to OPU compromised the in vitro embryo production in a program of OPU with a 7 d interval between sessions.